Investigating aspects of paternalistic leadership within the job demands-resources model - Lee, Michelle Chin Chin; Kee, Yun Jian; Lau, Samantha Shi Yea *; Jan, Ghulam (Cambridge University Press, 2023)
The literature on the job demands–resources (JD-R) theory has flourished for the past decade due to the theory's simplicity and its applications in many areas of work life. However, the literature is lacking on how leaders can utilize this theory to manage employees, especially in the Asian leadership context. Using the JD-R theory, the current study investigated each aspect of paternalistic leadership (i.e., benevolent leadership, authoritarian leadership and moral leadership) and its influence on employees' job resources (i.e., work meaningfulness and influence at work), job demands (i.e., emotional and cognitive demands), work engagement, burnout and the processes involved. Four hundred and thirty-one (431) full-time working employees (mean age: 31.58; female: 57.8%) from various organizations in Malaysia participated in the study. Using structural equation modelling, the study's results showed that the benevolent aspect of paternalistic leadership was related to higher work engagement and lower burnout through work meaningfulness (but not through influence at work). In contrast, the authoritarian aspect of paternalistic leadership was related to higher burnout through emotional demands (but not through cognitive demands), while the moral leadership aspect had no significant relationship to employees' job demands or job resources, with a mediation process not found in either relationship. Overall, the study revealed three contrasting mechanisms for each aspect of paternalistic leadership and suggested how paternalistic leadership may be practised in Asian countries.